Pomodoro, a mobile robot platform for hand motion exercising - Dos Reis Alves, Silas F.; Uribe-Quevedo, Alvaro J.; Da Silva, Ivan Nunes; Filho, Humberto Ferasoli [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
According to the World Report on Disability, currently 93 million children experience some kind of moderate or severe disability. Several systems including motion capture, serious games, exoskeletons and robotics have been researched and developed for assisting them on recovering basic functionality and daily activities, thus, improving mobility and providing a better quality of life. The popularization of these tools is a challenging task due to the required technical knowledge and the high acquisition costs, yet, the field of didactic robots is growing as an alternative that can be used in education, research, entertainment and other scenarios. This project proposes the development of the Pomodoro mobile robot as a device for encouraging hand motion exercise through flexion/extension and ulnar/radial deviation movements, for teleoperating the system in users experiencing reduced hand mobility. The system is composed of a low cost non-holonomic robot controlled with an embedded smartphone for on-site interactions through speech, image recognition and touch controls, along with a complimentary hand motion tracking subsystem for teleoperating the system using both real and virtual system, while recording position and orientation data for further assessment.